2011
DOI: 10.1001/archoto.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cx43 Gap Junction Plaque Expression Differentiates Thyroid Carcinomas From Benign Disease

Abstract: Our data provide evidence that the absence of Cx43 plaque staining is associated with thyroid cancer and thus holds potential clinical utility as a marker for malignant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It may be mediated through the Wnt signaling pathway, which has been shown for HT29 colorectal cancer cells [87] and for cells of non-tumorigenic breast epithelium HMT-3522 S1 [40]. Loss of connexin-43 may also drive malignant transformation, which was reported for benign thyroid tumors [88].…”
Section: Discussionmentioning
confidence: 86%
“…It may be mediated through the Wnt signaling pathway, which has been shown for HT29 colorectal cancer cells [87] and for cells of non-tumorigenic breast epithelium HMT-3522 S1 [40]. Loss of connexin-43 may also drive malignant transformation, which was reported for benign thyroid tumors [88].…”
Section: Discussionmentioning
confidence: 86%
“…Although TSH and thyroid hormones have been reported to regulate connexins in a variety of target tissues [142][143][144], their role in mediating thyroid function itself is not welldocumented. Indeed, connexin expression in the thyroid gland mainly controls cell differentiation and gland development, and most studies have been focused on the role of connexins in pathological situations [145][146][147].…”
Section: Thyroid and Parathyroid Glandsmentioning
confidence: 99%
“…It has been shown that TSH and TH regulate the expression of connexins in a variety of target tissues, including the thyroid gland [159]. Reduced connexin-43 expression in the thyroid tissue differentiates TCA from a benign disease and provides clinical utility as a marker for malignancy [160,161], while decreased connexin-43 protein abundance in the cardiac tissue in the experimental hyperthyroid setting increases the propensity to AF and VF [26,27,108,162]. On the other hand, the upregulation of atrial connexin-40 precedes AF as well [163].…”
Section: Of 19mentioning
confidence: 99%